Response of maize and cassava to potassium fertilization and alley cropping with Leucaena leucocephala and Acacia auriculiformis - Akonde, T.P.; Leihner, D.E.; Kang, B. (1995)
Field trials were carried out on a Dystric Nitosol at Calavi in the subhumid zone of southern Benin Republic, West Africa from 1989-1997. A split plot design with four replications was used. There were (our main plots: control (no hedgerow), Leucaena hedgerows, Acacia hedgerows and mixed Leucaena/Acacia hedgerows. Hedgerows were planted 4 m apart. Subplots consisted of three K rates (0, 37, 74 kg K ha-1). Maize and cassava were planted at populations of 40,000 and 10,000 plants ha-1, respectively. Plots received a basal dressing of 90 kg N ha-1 and 20 kg P ha-1. Maize and cassava showed significant responses to K fertilizer. Alley cropping with Acacia and Acacia/Leucaena mixed hedgerows gave lower maize and cassava root yields. In the third cropping year maize and cassava yields in no K plots were higher when alley cropped with Leucaena. It appeared that Leucaena prunings could provide enough K for higher maize and cassava yields.